CFD study of formation and rise characteristics of a single bubble in bubble column / Md.Tariqul Islam - Md. Tariqul, Islam (2015)
The volume of fluid with the continuum surface force (VOF-CSF) method has been used in the current numerical work to investigate the bubble formation and the bubble shape in a bubble column. The shape of the bubble has been tracked by using the piecewise linear interface calculation (PLIC). The effect of orifice sizes ranging from 0.5 mm to 1.5 mm on the bubble formation stages (i.e., expansion, elongation and pinch off), bubble contact angle, departure diameter, time and shape of bubble was investigated under a constant inlet velocity (0.2 m/s) boundary condition. It was found that a leading bubble required a longer time to detach from an orifice in comparison to the following bubbles, but interestingly the third bubble took quite longer time than the second bubbles. This model has also been used to study the effect of Bond number and Reynolds number on bubble formation. The velocity field around the bubble has a significant effect on bubble formation, when the Bond number and Reynolds numbers are changed. Moreover, the effect of trapezoidal type columns to the rise velocity of a single bubble was simulated using a couple level set volume of fluid (CLSVOF) method. The bubble rise velocity reduced with the increase of trapezoidal angle or with the decrease of the top column width. Subsequently, the bubble rising distance for a given particular total time reduced with the increase of the trapezoidal angle. The trapezoidal cavity enhanced the spatial or lateral distribution of a bubble to left and right of the column. The trapezoidal column also enhanced the change of bubble shape from elliptic to circle and vice versa with the increase of the time or the vertical height. Finally, the VOF-CSF method was applied to investigate the effect of non-dimensional liquid viscosity and the effect of non-dimensional surface tension coefficient on co-axial and parallel bubble coalescence as well as rise trajectories in stagnant liquid. It was found that the coalescence time of two co-axial bubbles decreased with the reducing surface tension coefficient and reducing liquid viscosity. For the parallel bubbles coalescence, non-dimensional critical flat gap of bubble coalescence (Sc) decreased with the increase of bubble diameter under reduction of surface tension coefficient. But Sc increased with reduction of liquid viscosity. When the initial flat gaps of bubble are larger from Sc; the parallel bubbles enchanted by its repulsive effect. The findings from these works may be able to provide a fundamental knowledge and also be useful for designing a sparger for bubble column reactors.